2022
DOI: 10.1002/nafm.10727
|View full text |Cite
|
Sign up to set email alerts
|

Status and Management of the Blue Crab Fishery in the Gulf of Mexico

Abstract: Management of the blue crab Callinectes sapidus fishery in the Gulf of Mexico is the responsibility of the individual states under the purview of a regional management plan. States generally follow the "2-S" system of management, placing emphasis on size and sex. Despite management policies, harvest and juvenile abundances remain in decline. A significant trend toward decreasing harvest began in the early 2000s, with landings below average in 13 of the 20 years from 2000 to 2019. Since 2010, the fishery has ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…2010; Perry et al. 2022). Maintaining balanced sex ratios within populations is important for their sustainability and to avoid potential impacts such as those related to male‐focused harvest, specifically when the commercial fishery is pot‐based (Carver et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010; Perry et al. 2022). Maintaining balanced sex ratios within populations is important for their sustainability and to avoid potential impacts such as those related to male‐focused harvest, specifically when the commercial fishery is pot‐based (Carver et al.…”
Section: Discussionmentioning
confidence: 99%
“…Management approaches for the blue crab frequently rely on an understanding of sex-specific abundances within populations, often leading to restrictions on female harvest (Eggleston et al 2009;Bunnell et al 2010;Perry et al 2022). Maintaining balanced sex ratios within populations is important for their sustainability and to avoid potential impacts such as those related to male-focused harvest, specifically when the commercial fishery is pot-based (Carver et al 2005;Ogburn et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, blue crab populations in much of the northern Gulf of Mexico have experienced declining trends over the past decades, specifically related to depressed juvenile abundance (Perry et al. 2022). This has been especially apparent in Texas waters (Sutton and Wagner 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This could include competition with species that share a similar trophic role, such as Hardhead Catfish (Pensinger et al 2021), and increased predation on species such as blue crabs Callinectes sapidus and penaeid shrimp that are both valuable fishery organisms and important prey items for many other species. Notably, blue crab populations in much of the northern Gulf of Mexico have experienced declining trends over the past decades, specifically related to depressed juvenile abundance (Perry et al 2022). This has been especially apparent in Texas waters (Sutton and Wagner 2007).…”
Section: Model and Bay Systemmentioning
confidence: 99%
“…Various authors reported similar linear relationships between these parameters while conducting a study on different sh species, viz. Perry and Vanderkooy (2015), Hema et al (2012), Bithy et al (2012), Singh (2009), Somdutt and Kumar (2004). Although these factors were not taken into account for this study due to the small number of female specimens with different ovarian-maturation stages, other factors such as condition, Gonadosomatic index, and OW were counted.…”
Section: Reproductive Physiologymentioning
confidence: 99%